Study of GeSn Mid-infrared Photodetectors for High Frequency Applications - Tran, Huong; Littlejohns, Callum G.; Thomson, David J.; Pham, Thach; Ghetmiri, Amir; Mosleh, Aboozar; Margetis, Joe; Tolle, John; Mashanovich, Goran Z.; Du, Wei; Li, Baohua; Mortazavi, Mansour; et al. (Frontiers in Materials, 2019)
In 2016, Thach et al. reported figures of merit of the GeSn photodiodes with large mesa sizes of 500 and 250 µm to show the potential of the GeSn materials in short-wave infrared photonics.23 However, there are only a few discussions about high frequency capabilities of GeSn photodetectors. It is needed to understand the potential of GeSn detectors as high frequency devices. This paper discusses comprehensively about the performance of GeSn photodiodes with 6.44 % and 9.24 % Sn for high frequency applications including high speed measurements and simulations. 6.449.24 %. With high Sn incorporation, the cutoff wavelength is extended up to 2.2 μm and 2.5 μm wavelengths for 6.44 % and 9.24 % Sn devices, respectively. The photodiodes’ bandwidth is 1.78 GHz, and the simulation shows excellent agreement with measurement results. The reported GeSn photodetectors together with recently reported GeSn lasers and other GeSn microwave photonic components will be a potential candidate for integrated microwave photonics.